CFD models comparative study on nanofluids subcooled flow boiling in a vertical pipe - Behroyan, Iman; Ganesan, Poo Balan; He, Shuisheng; Sivasankaran, Sivanandam (Taylor & Francis, 2018)
The effects of subcooled flow boiling of nanofluids (Al2O3/water and Cu/water) through a vertical heated pipe are investigated numerically considering a number real flow factors such as uneven particle distributions and particle deposition on the wall surface. The results from the Eulerian–Eulerian two-phase model (liquid/nanofluid–gas) and those of the Eulerian–Lagrangian three-phase model (liquid–gas particles) are compared in detail. For the heat transfer coefficient prediction, the latter model gives about 6% error, whereas the Eulerian–Eulerian model gives about 12% error when it is compared with Chen’s correlation. The uneven distribution of nanoparticles concentrations, i.e., lower near the tube wall and higher at the pipe center, is well predicted by the Eulerian–Lagrangian model. On top that, for the first time, the changes on heating surface wettability induced by nanoparticles deposition is included via user define functions.